5′‐ectonucleotidase mediates multiple‐drug resistance in glioblastoma multiforme cells1. Issue 3 (23rd November 2012) - Quezada, Claudia; Garrido, Wallys; Oyarzún, Carlos; Fernández, Katia; Segura, Rodrigo; Melo, Rómulo; Casanello, Paola; Sobrevia, Luis; San Martín, Rody
Abstract Glioblastoma multiforme (GBM) cells are characterised by their extreme chemoresistance. The activity of multiple‐drug resistance (MDR) transporters that extrude antitumor drugs from cells plays the most important role in this phenomenon. To date, the mechanism controlling the expression and activity of MDR transporters is poorly understood. Activity of the enzyme ecto‐5′‐nucleotidase (CD73) in tumor cells, which hydrolyses AMP to adenosine, has been linked to immunosuppression and prometastatic effects in breast cancer and to the proliferation of glioma cells. In this study, we identify a high expression of CD73 in surgically resected samples of human GBM. In primary cultures of GBM, inhibition of CD73 activity or knocking down its expression by siRNA reversed the MDR phenotype and cell viability was decreased up to 60% on exposure to the antitumoral drug vincristine. This GBM chemosensitization was caused by a decrease in the expression and activity of the multiple drug associated protein 1 (Mrp1), the most important transporter conferring multiple drug resistance in these cells. Using pharmacological modulators, we have recognized the adenosine A3 receptor subtype in mediation of the chemoresistant phenotype in these cells. In conclusion, we have determined that the activity of CD73 to trigger adenosine signaling sustains chemoresistant phenotype in GBM cells. J. Cell. Physiol. 228: 602–608, 2013. © 2012 Wiley Periodicals, Inc.